Trauma-Focused Interventions for Justice-Involved and At-Risk Youth: A Meta-Analysis, 1980-2015 - Wilson, David B. ([Verlag nicht ermittelbar], 2020)
The objective of the Trauma-Focused Interventions for Justice-Involved and At-Risk Youth meta-analysis was to systematically review and statistically synthesize all available research on the effectiveness of trauma-informed treatment programs for justice-involved youth and youth at-risk of justice system involvement who experienced some form of trauma in their lives. A systematic search identified 29 publications that met the eligibility criteria and represented 30 treatment-comparison contrasts. Of these studies, 6 evaluated the effectiveness of trauma-informed programs for justice-involved youth, and the remaining 24 evaluated programs for at-risk children and youth. From these studies, researchers extracted results related to delinquency, problem behaviors, aggression, antisocial behavior, substance use, and post-traumatic stress disorder (PTSD) outcomes. Most of these studies (24) used random assignment to conditions designs, with the remaining 6 using a quasi experimental design with a comparison condition. Variables in this collection include type of publication, authors, country of study, type of primary study design, publication year, youth type (at-risk or delinquent), frequency and duration of treatment, treatment techniques and types of therapy, treatment and control group sample sizes, as well as variables summarizing respondent histories of abuse, neglect, trauma, violence, delinquency, institutionalization, homelessness, and involvement in foster care. Demographic information on primary study respondents includes overall sample, treatment, and control group percentage breakdowns by ethnicity and respondent age summary statistics.